KOLABORASI BAHASA DAN KULINER: MEMPERKUAT DAYA TARIK WISATA KULINER DESA - Ayu Melistyari Dewi, I Gusti; Isha Aprinica, Ni Putu; Muliadiasa, I Ketut; Ayu Gayatri Kesumayathi, Ida; Agustina, Arik (Berajah Journal, 2024)
In this era of globalization full of competition, Serangan Village needs to continue to innovate and increase its attractiveness to attract more tourists. One promising strategy is to combine language and cuisine, creating a unique and unforgettable culinary tourism experience. The research method used in this research is a qualitative research method with data collection techniques, namely observation, interviews and documentation. The results of this research show that community participation through language and culinary arts is able to strengthen the tourist attraction for culinary delights in Serangan Village. The right strategy could be to empower POKDARWIS, especially those who can speak English, in collaborative language and culinary activities in Village.